The cognitive-affective-conative model of destination image: A confirmatory analysis - Agapito, Dora (2012)
Destination image influences tourist behaviour before, during and after travel, as it is an important instrument which contributes to tourists’ loyalty. In this context, although Gartner (1993) advocates that the cognitive, affective and conative dimensions of destination image are hierarchically interrelated, there is no empirical evidence to support the complete model. This study aims to test the hierarchical nature of the relationship between the dimensions of destination image. The results of structural equation modelling (SEM) confirm Gartner’s (1993) theoretical model, validating the theory that the influence of the cognitive component on the conative dimension is stronger when mediated by the affective component. This conclusion raises important considerations regarding affect as a crucial aspect linking destinations and people.